Strategi Komunikasi Pemasaran (Marketing Mix) Pada Kasmaran Wedding Organizer - Anngelina Cindy Mega Pramita; Dyva Claretta (Yayasan Perguruan Kampus, 2024)
Marketing mix is ​​an effort to convey messages to the public, especially consumers, regarding the existence of a product on the market. This research examines the marketing strategy carried out by Kasmaran Wedding Organizer using qualitative research methods and integrated interviews with the Owner, Project Manager and Marketing Manager of Kasmaran Wedding Organizer. The purpose of this research is to determine the marketing strategy (marketing mix) carried out by Kasmaran Wedding Organizer. The results of this research show that the products offered by Kasmaran Wedding Organizer are wedding organization service products for both modern and traditional weddings. The prices offered by Kasmaran Wedding Organizer start from IDR 15,000,000, and can be adjusted to the client's needs. Social Media is the spearhead of promotion for Kasmaran Wedding Organizer. Kasmaran Wedding Organizer was founded in Pacitan Regency because Pacitan Regency is a strategic place for the wedding organizer business. The recruitment process of the Kasmaran Organizer Crew is carried out quite selectively so that it can boost the work process and marketing process of the Kasmaran Wedding Organizer. The process of establishing Kasmaran Wedding Organizer was initially only a main crew but now has many crew. Instagram and promotional brochures are physical evidence of the Kasmaran Wedding Organizer marketing process. The strength of Kasmaran Wedding Organizer lies in the quality of the crew and vendors offered. The weakness is that the promotion process is only carried out on social media. The opportunity that Kasmaran Wedding Organizer can take advantage of is that there are not many professional Wedding Organizers in Pacitan and the threat that exists is the large number of competitors who offer prices that are too low and a few people who hardly to understand about what wedding organizer is.